Optical properties of plasmonic nanopore arrays prepared by electron beam and colloidal lithography. Issue 11 (16th October 2019) - Malekian, Bita; Xiong, Kunli; Kang, Evan S. H.; Andersson, John; Emilsson, Gustav; Rommel, Marcus; Sannomiya, Takumi; Jonsson, Magnus P.; Dahlin, Andreas
Abstract : We present new plasmonic nanopore arrays and their optical properties, in particular the influence from short-range vs. long-range ordering. Abstract : Solid state nanopores are central structures for many applications. To date, much effort has been spent on controlled fabrication of single nanopores, while relatively little work has focused on large scale fabrication of arrays of nanopores. In this work we show wafer-scale fabrication of plasmonic nanopores in 50 nm thick silicon nitride membranes with one or two 30 nm gold films, using electron beam lithography with a negative resist or a new version of colloidal lithography. Both approaches offer good control of pore diameter (even below 100 nm) and with high yield (>90%) of intact membranes. Colloidal lithography has the advantage of parallel patterning without expensive equipment. Despite its serial nature, electron beam lithography provides high throughput and can make arbitrary array patterns. Importantly, both methods prevent metal from ending up on the membrane pore sidewalls. The new fabrication methods make it possible to compare the optical properties of structurally identical plasmonic nanopore arrays with either long-range order (e-beam) or short-range order (colloidal). The resonance features in the extinction spectrum are very similar for both structures when the pitch is the same as the characteristic spacing in the self-assembled colloidal pattern. Long-range ordering slightly enhances the magnitude of the extinction maximum and blueshift the transmission maximum by tens of nm. Upon reducing the diameter in long-range ordered arrays, the resonance is reduced in magnitude and the transmission maximum is further blue shifted, just like for short-range ordered arrays. These effects are well explained by interpreting the spectra as Fano interference between the grating-type excitation of propagating surface plasmons and the broad transmission via individual pores in the metal film. Furthermore, we find that only the short-range ordered arrays scatter light, which we attribute to the highly limited effective period in the short-range ordered system and the corresponding lack of coherent suppression of scattering by interference effects.